Endocrine and Neuroendocrine Cancers - Berruti, Alfredo; Amoroso, Vito; Fazio, Nicola (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Endocrine and neuroendocrine tumors originate from endocrine cells but are heterogeneous in terms of clinical presentation, disease outcome, and treatments available. This Special Issue addresses specific aspects of pre-clinical, clinical, and translational research and clinical management of these diseases with the aim of providing novel insights, addressing current unmet needs, and discussing future treatment perspectives.